Workshop Pengelolaan Jurnal dalam Lingkup Prodi Pendidikan Matematika - Dian Permatasari (Abdimas Mandalika, 2022)
Abstract:  Community service is an effort to share knowledge about journal management for journal managers so that they can manage journals properly and correctly. This service is carried out by holding a workshop followed by a journal review. used are workshops and journal surgery. The workshop was held twice and continued with journal review to find out the shortcomings of each journal. The methods used are workshops and journal surgery. The results obtained during the journal management workshop were that the participants knew the management of the journal from a managerial perspective as well as from an article editing perspective. It is hoped that after obtaining the journal management workshop, participants can prepare their journals for national and international accreditation. Improving the quality of scientific journal management is one of the basic components that greatly affects the quality of published journals. Journal managers who are not equipped with good journal management skills will certainly not be able to carry out a good journal management process. This Community Service (PkM) activity carried out in the Mathematics Education Study Program is very useful for journal managers. Especially for managers who have planned to submit their journals to register with the National Journal Accreditation (Arjuna) BRIN. This PkM is also an opportunity for journal managers to correct deficiencies in their respective journals. After understanding what are the shortcomings in the journals that are managed, it will be easier to fix them. Abstrak: Pengabdian kepada masyarakat merupakan salah satu upaya untuk sharing pengetahuan mengenai pengelolaan jurnal bagi para pengelola jurnal agar dapat mengelola jurnal dengan baik dan benar. Pengabdian ini dilakukan dengan mengadakan workshop dilanjutkan dengan bedah jurnal. yang digunakan adalah workshop dan bedah jurnal. Workshop dilaksanakan sebanyak dua kali dan dilanjutkan dengan bedah jurnal untuk mengetahui kekurangan dari masing-masing jurnal. Hasil yang diperoleh selama workshop pengelolaan jurnal adalah peserta mengetahui pengelolaan jurnal dari segi managerial maupun dari segi penyuntingan artikel. Kegiatan Pengabdian kepada Masyarakat (PkM) yang dilaksanakan di Prodi Pendidikan Matematika ini, sangat bermanfaat sekali bagi para pengelola jurnal. Terutama bagi pengelola yang sudah merencanakan untuk mengajukan jurnalnya mendaftar pada Akreditasi Jurnal Nasional (Arjuna) BRIN. PkM ini juga menjadi ajang bagi para pengelola jurnal untuk memperbaiki kekurangan-kekurangan pada jurnal mereka masing-masing. Setelah memahami apa yang menjadi kekurangan pada jurnal yang dikelola, maka akan lebih mudah untuk memperbaikinya.